Optimised laser microdissection of the human ocular surface epithelial regions for microarray studies - Kulkarn, Bina B .; Powe, Desmond G.; Hopkinson, Andrew; Dua, Harminder S. (BioMed Central, 2013)
Background The most important challenge of performing insitu transcriptional profiling of the human ocular surface epithelial regions is obtaining samples in sufficient amounts, without contamination from adjacent tissue, as the region of interest is microscopic and closely apposed to other tissues regions. We have effectively collected ocular surface (OS) epithelial tissue samples from the Limbal Epithelial Crypt (LEC), limbus, cornea and conjunctiva of post-mortem cadaver eyes with laser microdissection (LMD) technique for gene expression studies with spotted oligonucleotide microarrays and Gene 1.0 ST arrays.